Sorption of carbendazim on activated carbons derived from rape straw and its mechanism. Issue 71 (17th December 2019) - Wang, Tao; Zhang, Zhen; Zhang, Huixue; Zhong, Xiaoxiao; Liu, Yonghong; Liao, Shuijiao; Yue, Xiali; Zhou, Guangsheng
Abstract : Due to the production and widespread application of pesticides, pesticide pollution poses a potential danger to human health and the ecosystem. Abstract : Due to the production and widespread application of pesticides, pesticide pollution poses a potential danger to human health and the ecosystem. Herein, activated carbons employing rape straw as a precursor were produced using H3 PO4 as an activating agent at various temperatures (300–600 °C). The activated carbons differed with respect to the physicochemical properties, which were derived from elemental analysis, N2 sorption–desorption, FTIR, XPS, XRD, pHpzc, Boehm titration and blocking of the oxygen-containing groups. The oxygen-containing functional groups and the pore structure of the activated carbons obtained from the different preparation conditions were quite different. The as-prepared samples were applied as sorbents to remove carbendazim (CBD). The results indicated that the sorption of CBD was mainly dominated by partitioning at low concentrations of CBD. Meanwhile, electrostatic attractions played a more important role than hydrophobic interactions at a low initial pH; in contrast, as the initial pH increased, the hydrophobic interaction was the predominant sorption mechanism. Therefore, the results can be used to design some efficient and environmentally friendly adsorbents to reduce the risk of organic pollutants, especially organic pesticides, in aqueous solutions.